Ovarian superstimulation after ablation and steroid induced follicular wave synchronization in zebu cattle* - RAO, M MUTHA; UMAMAHESH, Y; NAIDU, K VENUGOPAL; RAO, K BABU; MISHRA, A K (The Indian Journal of Animal Sciences, 2011)
The study was undertaken to determine if superovulation (Sov) subsequent to induction of follicular wave emergence could be used as an alternative to conventional protocol in Ongole cows. The donors were randomly placed in group 1 (control group, n=15), Sov was initiated on day 10 (day zero, day of estrus) of the estrous cycle; group 2 (ablation group, n=13) cows, the dominant follicle (DF) was ablated on day 8 of the cycle followed by Sov 48h later; group 3 (steroid group, n = 17), donors received a progestational implant 4 days before the start of Sov treatment. Superovulation treatment involved administration of 200 mg NIH-FSH-!1 twice daily in a descending dose schedule for 4 days and induction of luteolysis at 48h (PGF1) and 60h (PGF2) after initiating treatment. In Group 3 cows the implant was removed 12h after PGF1. Non-surgical embryo collection was performed on day 7 after superestrus. The ovulation rate was significantly higher in ablation group (15.08±1.5) over steroid group (10.37±0.82). However, no significant difference was observed in ovulation rate between control group (13.53±1.80) and other 2 groups. In spite of low ovulation rate in steroid group, a high percentage of total embryo recovery (83.13%) and proportionately higher viable embryo yield (76.81%) in this group resulted in a nonsignificant difference in total and viable embryos recovery among the 3 groups. The total embryo recovery in the 3 groups, respectively, was 9.4±2.04, 10.17±1.78 and 8.63±0.88 and the viable embryo recovery 6.8±1.74, 7.25±1.40 and 6.63±0.82. Similarly, there was no significant difference in fertilization rate as well as number of grade I embryos among the groups. The study demonstrated that induction of follicular wave emergence prior to superovulation both by physical (ablation) and hormonal (steroid) methods can be safely used in zebu donors, and had no adverse effect on fertilization rate and viable embryo yield.